2015
DOI: 10.1016/j.ijpsycho.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

How does reactivity to frustrative non-reward increase risk for externalizing symptoms?

Abstract: Frustration is a normative affective response with adaptive value in motivating behavior. However, excessive anger in response to frustration characterizes multiple forms of externalizing psychopathology. How a given trait subserves both normative and pathological behavioral profiles is not entirely clear. One hypothesis is that the magnitude of response to frustration differentiates normative versus maladaptive reactivity. Disproportionate increases in arousal in response to frustration may exceed normal regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…Of note, children with BD exhibited frustration-induced arousal similar to the SMD group suggesting that this response may not be specific to chronic irritability. This is further supported by physiological studies showing that children with conduct (Gatzke-Kopp, Willner et al, 2015; Wang, Guo, You, & Gao, 2007) and other externalizing (Woltering et al, 2016) problems exhibit increased heart rate during frustration, as compared to healthy controls. Thus, children with clinically significant irritability may be particularly vulnerable to feelings of frustration; given the frequency with which frustration is encountered in our daily lives, this would likely lead to increased temper outbursts and significant functional impairment.…”
Section: Frustration Reward and Non-rewardmentioning
confidence: 74%
See 1 more Smart Citation
“…Of note, children with BD exhibited frustration-induced arousal similar to the SMD group suggesting that this response may not be specific to chronic irritability. This is further supported by physiological studies showing that children with conduct (Gatzke-Kopp, Willner et al, 2015; Wang, Guo, You, & Gao, 2007) and other externalizing (Woltering et al, 2016) problems exhibit increased heart rate during frustration, as compared to healthy controls. Thus, children with clinically significant irritability may be particularly vulnerable to feelings of frustration; given the frequency with which frustration is encountered in our daily lives, this would likely lead to increased temper outbursts and significant functional impairment.…”
Section: Frustration Reward and Non-rewardmentioning
confidence: 74%
“…When a child anticipates a reward and the reward is omitted, a negative affective state ensues (i.e. “frustration”) and typically manifests in the form of aggression (Gatzke-Kopp, Willner, Jetha, Abenavoli, DePuis, & Segalowitz, 2015). The aggressive reaction, such as a temper tantrum, encompasses changes in affective arousal, cognitive control, physiology, and dopaminergic processes (Hubbard et al, 2002; Schoemaker, Mulder, Dekovic, & Matthys, 2013; Deveney et al, 2013; Kreibig, 2010).…”
Section: Frustration Reward and Non-rewardmentioning
confidence: 99%
“…Some other recent studies have reported that P3b amplitudes are larger following unanticipated nonreward feedback than following anticipated reward feedback (Gatzke‐Kopp et al, ; Rich et al, ). The present research extended these findings, showing that increases in P3b amplitude occur for inconsistent outcomes that are frustrating and nonfrustrating (but instead pleasantly surprising).…”
Section: Discussionmentioning
confidence: 96%
“…In each study, anger was produced by including blocks of trials that yielded an increased proportion of nonreward or loss feedback relative to preceding blocks. Participants reported greater frustration on these blocks of trials (Rich et al, 2007) and had larger P3b amplitudes for frustrating outcomes than for nonfrustrating outcomes (Gatzke-Kopp et al, 2015;Rich et al, 2007Rich et al, , 2005. Despite these promising results, these methods have limitations and interpretive caveats.…”
Section: Evoking Anger In the Labmentioning
confidence: 99%
“…It should be noted that RDoC-informed research may use between-groups analyses, but the groupings should be based on the presence of naturally-occurring discontinuities or ‘tipping points’ that are discovered by studying the full range of variation in the construct of interest. Gatzke-Kopp and colleagues (2015 - this issue) provide an example of hierarchical analyses examining relationships among differing behavioral and physiological measures, leading to integrative conclusions regarding the autonomic and cognitive responses to frustration associated with conduct problems in children. Shankman and Gorka (2015 - this issue) highlight a distinct analytic and interpretive complication inherent to developmental hypotheses, namely: Are RDoC constructs predictors of change in symptoms over time, or static markers of current pathology?…”
mentioning
confidence: 99%